Additional records of decapod crustaceans from the lower Pleistocene beds of Poggi Gialli (Tuscany, central Italy) - Pasini, Giovanni; Garassino, Alessandro; de Angeli, Antonio; Pizzolato, Francesco (Geologija, 2020)
Additional species of decapod crustaceans are recorded from the lower Pleistocene beds exposed at the Poggi Gialli quarries (Sinalunga, Tuscany, central Italy). They include Galathea tuscia sp. nov., Ilia sp., Liocarcinus cf. L. maculatus (Risso, 1827), and Aliaplax tyrsenorum gen. nov., sp. nov. Novel morphological details for Distolambrus rasnus De Angeli, Garassino & Pasini in Baldanza, Bizzarri, De Angeli, Famiani, Garassino, Pasini & Pizzolato, 2017, based on a single newly collected specimen, are added, as is the rare record of an indeterminate nephropid. These additions augment our knowledge of the composition of carcinological faunas in this peculiar environment from the early Pleistocene of central Italy. An updated list of decapod crustacean species from Poggi Gialli is also provided herein.